Regulation of Nutrient Transport across the Placenta - Lager, Susanne (Hindawi Publishing Corporation, 2012)
Abnormal fetal growth, both growth restriction and overgrowth, is associated with perinatal complications and an increased risk of metabolic and cardiovascular disease later in life. Fetal growth is dependent on nutrient availability, which in turn is related to the capacity of the placenta to transport these nutrients. The activity of a range of nutrient transporters has been reported to be decreased in placentas of growth restricted fetuses, whereas at least some studies indicate that placental nutrient transport is upregulated in fetal overgrowth. These findings suggest that changes in placental nutrient transport may directly contribute to the development of abnormal fetal growth. Detailed information on the mechanisms by which placental nutrient transporters are regulated will therefore help us to better understand how important pregnancy complications develop and may provide a foundation for designing novel intervention strategies. In this paper we will focus on recent studies of regulatory mechanisms that modulate placental transport of amino acids, fatty acids, and glucose.